Optimizing clinical outcomes for bronchoscopic lung volume reduction with Zephyr® valves - Koster, David; Shah, Pallav L.; Valipour, Arschang; Criner, Gerard J.; Herth, Felix; Sue, Richard; Hogarth, Douglas K.; Martin, Ralitza T.; Mahajan, Amit K.; Alalawi, Raed; Kopas, Lisa; Cohen, Avi; et al. (Respiratory medicine, 2024)
Bronchoscopic lung volume reduction treatment with Zephyr one-way valves is an effective guideline-based treatment option for patients with severe emphysema and hyperinflation. However, in some cases the treatment response is less than anticipated or there might be a loss of initial treatment effect. Reasons for the lack of response can include incorrect assessment of collateral ventilation, improper valve placement, or patient related factors. Loss of initial benefit can be due to granulation tissue formation and subsequent valve dysfunction, or there may be side effects such as excessive coughing or infectious problems. Careful follow-up after treatment with valves is important and evaluation with a CT scan and/or bronchoscopy is helpful if there is no improvement after treatment or loss of initial benefit. This paper aims to describe the most important causes and provide a strategy of how to approach and manage these patients.